1995
DOI: 10.1097/00005373-199502000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Extraperitoneal Rectal Gunshot Injuries

Abstract: Extraperitoneal rectal gunshot injuries are rare, but may be encountered in civilian practice. We report on a series of 26 such cases. The aim of the study is to attempt to evolve a treatment policy of this injury. The principles of management include the repair of rectal wound in selected cases and the formation of a diverting colostomy. Distal rectal washout and presacral drainage, although advocated by some authors, do not seem to be indispensable adjuncts to the management of these injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
6

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 13 publications
0
21
0
6
Order By: Relevance
“…Mientras ha habido en general acuerdo en el uso de la colostomía de detransitación para las lesiones del recto extraperitoneal 7,18,20,35,36 , para el drenaje presacro y el lavado rectal distal en cambio ha surgido un prolongado análisis con respecto a su efectividad para reducir complicaciones infecciosas en el trauma rectal penetrante civil 20,34 . Mientras varios autores continuaban preconizando el drenaje presacro sistemático 7,34,37 otros creían que su uso debía ser selectivo según las características de las lesio-nes 20,35,38,39,40 .…”
Section: Abcddv/581unclassified
See 3 more Smart Citations
“…Mientras ha habido en general acuerdo en el uso de la colostomía de detransitación para las lesiones del recto extraperitoneal 7,18,20,35,36 , para el drenaje presacro y el lavado rectal distal en cambio ha surgido un prolongado análisis con respecto a su efectividad para reducir complicaciones infecciosas en el trauma rectal penetrante civil 20,34 . Mientras varios autores continuaban preconizando el drenaje presacro sistemático 7,34,37 otros creían que su uso debía ser selectivo según las características de las lesio-nes 20,35,38,39,40 .…”
Section: Abcddv/581unclassified
“…Mientras varios autores continuaban preconizando el drenaje presacro sistemático 7,34,37 otros creían que su uso debía ser selectivo según las características de las lesio-nes 20,35,38,39,40 . Otro tanto sucedió con el uso del lavado rectal distal, apoyado por algunos para ser empleado siempre 38,41 mientras que otros solo lo llevaban a cabo en casos seleccionados 7,20,34,35,40 . De este modo llegamos hasta la actualidad, en la cual existe falta de consenso con respecto al óptimo manejo quirúrgico del TRE 36 en el medio civil.…”
Section: Abcddv/581unclassified
See 2 more Smart Citations
“…Levy et al [21] reported the length of hospital stay to be 21 days (range: 10 days to 4 months) in civilian extraperitoneal rectal injury cases. The length of hospital stay in the present study ranged from 5-51 days and was 27.0±12.4 days on average in Group 1.…”
mentioning
confidence: 99%